2006
DOI: 10.1001/archinte.166.6.651
|View full text |Cite
|
Sign up to set email alerts
|

Natural History of Knee Cartilage Defects and Factors Affecting Change

Abstract: Background: Knee cartilage defects may play an important role in early osteoarthritis, but little is known about their natural history.Methods: Knee cartilage defect score (range, 0-4), cartilage volume, and bone surface area were determined using T1-weighted fat-saturated magnetic resonance imaging in 325 subjects (mean age, 45 years) at baseline and 2 years later.Results: Thirty-three percent of the subjects had a worsening (Ն1-point increase) and 37% of the subjects had an improvement (Ն1-point decrease) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
163
2
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 152 publications
(186 citation statements)
references
References 24 publications
16
163
2
5
Order By: Relevance
“…Previous studies have shown that cartilage volume loss is a more sensitive and specific marker of cartilage integrity than JSN and possibly the best outcome measure for drug trials looking to preserve cartilage (17). Moreover, cartilage defects have an unstable natural history as they can improve without any intervention depending on the age of the patient, especially in people with less advanced disease (14,26). This is a possible explanation of weaker associations we observed in our study compared to previously available literature.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…Previous studies have shown that cartilage volume loss is a more sensitive and specific marker of cartilage integrity than JSN and possibly the best outcome measure for drug trials looking to preserve cartilage (17). Moreover, cartilage defects have an unstable natural history as they can improve without any intervention depending on the age of the patient, especially in people with less advanced disease (14,26). This is a possible explanation of weaker associations we observed in our study compared to previously available literature.…”
Section: Discussioncontrasting
confidence: 68%
“…MRI. MRI of the right knee was performed as described previously (12)(13)(14). Knees were imaged in the sagittal plane on a 1.5T whole-body MR unit (Picker International), using a commercial transmit-receive extremity coil at the baseline visit and at the 2-year and 10-year followup visits.…”
Section: Significance and Innovationsmentioning
confidence: 99%
“…[20][21][22] To assess the reproducibility and consistency of our full-thickness injury model, the sections were investigated on the day of the operation. Although the CVs of cartilage thickness, depth of cartilage injury, and crosssectional width were more than 10%, CVs of %depth were all less than 10%.…”
Section: Discussionmentioning
confidence: 99%
“…Cartilage defects in these studies have been assessed by different trained readers who were blinded with regard to clinical data, demonstrating high methodologic quality; for a cartilage defect to be identified it also had to be present on 2 consecutive slices, further reducing measurement error. We have also shown that our method of assessment is sensitive to change over time (8). Additionally, it is convenient and cost-effective to use the same sequences for assessing both cartilage defects and cartilage volume.…”
Section: To the Editormentioning
confidence: 84%
“…It would not result in spurious associations. As is important for any measure, the reproducibility and reliability of our method is high in multiple settings (6)(7)(8)(9), and there is a moderate correlation with histologic findings (10). Most importantly, our measure of cartilage defects has also been shown to be associated with clinically important outcomes such as pain, radiographic OA, cartilage volume loss, cartilage breakdown markers, bone marrow lesions, and knee replacement surgery (11) in multiple cross-sectional and longitudinal studies.…”
Section: To the Editormentioning
confidence: 98%